CASE SERIES - INSULIN INFUSION THERAPY IS EFFECTIVE IN HYPERTRIGLYCERIDEMIAINDUCED ACUTE PANCREATITIS - DADASAHEB, MAINDAD; SUKHADYAL, DUHAN; AKHIL, NAGPAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Hypertriglyceridemia (HTG) is responsible for up to 10% of all acute pancreatitis (AP) cases. The objective of this study is to present the effects of insulin infusion therapy in HTG-induced AP. Methods: We had 11 patients with AP and high triglycerides between June 2020 and January 2021 admitted to Bharati Vidyapeeth Medical College and Hospital in Pune, Maharashtra, India. Following laboratory and imaging evaluations, all patients were treated with insulin infusions and supportive care. Following the achievement of triglyceride (TG) level <1000 mg/dL, patients were given Fenofibrate 160 mg OD and Saroglitazar 4 mg OD. We observed their recuperation during the treatment duration. Results: Our study included 11 AP patients ranging from 18 to 50 years of age, five men and six females. This group included diverse patient population obese, non-obese, diabetic, and non-diabetic patients. TG values ranged from 2200 to 8000 mg/dL, with a mean of 5345.4±1203.8 mg/dL. There were nine patients with moderate pancreatitis, two with mild pancreatitis, and none with severe pancreatitis. Insulin infusions in the range of 302–1008U were required for 2–4 days. TG dropped 17–41% on the 2nd day of insulin infusion and 59–75% on the 3rd day. In all patients, TG levels fell below 1000 mg/dL after 4 days of insulin infusion, and then they were treated with oral anti-lipid medications. Hospital stay ranged from 9 to 25 days, with a 100% recovery rate. Conclusion: Insulin infusion can be used to treat HTG-induced AP with minimal risk of complications.